Relationship between infant hypothyroidism and maternal thyroid disease - Mirzarahimi, Mehrdad; Barak, Manouchehr; Katebi, Leila; Kamran, Aziz; Moghaddam, Sanaz S. (International Journal Of Community Medicine And Public Health, 2023)
Background: Due to the very high complications of neonatal hypothyroidism in the country, neonatal screening program is performed for timely diagnosis and treatment of neonates. The aim of this study to investigate the relationship between infant hypothyroidism and maternal thyroid disease. Methods: This cross-sectional study was done on 195 neonates with a diagnosis of hypothyroidism. Necessary data were collected by a checklist and then analyzed by statistical methods in statistical package for the social sciences (SPSS) version 21 by statistical methods. Results: Of all mothers, 21.0% had a history of thyroid disease. There was no statistically significant relationship between maternal age and infant thyroid stimulating hormone (TSH). There was no significant relationship between the history of maternal hypothyroidism and maternal hypothyroidism (during experiments) with the amount of TSH in the newborn. There was a direct and significant relationship between maternal TSH level and maternal free T4. But there was no statistically significant relationship between infant TSH level and maternal TSH level and free T4. There was no significant difference in neonatal TSH levels with maternal anti-TPO status. There was no significant relationship between the history of maternal diabetes and the history of maternal hypertension with neonatal TSH. There was no significant difference in neonatal TSH levels by maternal thyroid status. Conclusions: In the present study, no significant relationship was found between the incidence of neonatal hypothyroidism and the presence of thyroid disease in mothers. The existence of different genetic and environmental factors and the significant impact of each of these factors can justify this result.